First-Time Mothers’ Enjoyment of Breastfeeding Correlates with Duration of Breastfeeding, Sense of Coherence, and Parental Couple and Child Relation: A Longitudinal Swedish Cohort Study - Agnes Granberg; Anette Ekström-Bergström; Caroline Bäckström (Nursing Research and Practice)
Objectives. Many women do not reach their own breastfeeding goals regarding duration of breastfeeding. Different factors influence breastfeeding, and to learn more about breastfeeding within a multidimensional and longitudinal perspective, further research is needed. Therefore, the aim of the present study was to investigate diverse factors correlated with first-time mothers’ enjoyment of breastfeeding and breastfeeding duration, between childbirth and two years after birth. Methods. In a prospective longitudinal cohort study, 324 newly become mothers were followed. The Spearman correlation test was used to investigate factors correlated with the degree to which mothers enjoy breastfeeding and the duration of breastfeeding. The Mann–Whitney test was conducted for comparisons of demographic characteristics between mothers who did or did not breastfeed. Results. Among the mothers, 99.2% initiated breastfeeding after birth. Frequencies of breastfeeding were 54.8% at six months, 9.1% at one year, and 1.0% at two years. The degree to which the mother enjoyed breastfeeding was correlated positively with (1) the duration of breastfeeding, (2) more positive feelings for and relation to the child, (3) the partner’s perceived relation to the child, (4) a higher sense of coherence, and (5) stronger perceived parental couple’s relationship. Longer breastfeeding duration was correlated positively with (1) a higher degree of enjoyment of breastfeeding, (2) more positive relation to the child, and (3) stronger perceived parental couple’s relationship. Additionally, breastfeeding during the first two hours after birth, more positive feelings for and relation to the child, and a higher degree of enjoyment of breastfeeding were more frequently reported among breastfeeding mothers, in comparison with not breastfeeding mothers. Conclusion. Mothers’ subjective experience from breastfeeding, sense of coherence, and couple relationship with partner and relationship with the child are valuable factors in regard to breastfeeding.